2020
DOI: 10.3322/caac.21604
|View full text |Cite
|
Sign up to set email alerts
|

The Affordable Care Act and access to care across the cancer control continuum: A review at 10 years

Abstract: Lack of health insurance coverage is strongly associated with poor cancer outcomes in the United States. The uninsured are less likely to have access to timely and effective cancer prevention, screening, diagnosis, treatment, survivorship, and end-of-life care than their counterparts with health insurance coverage. On March 23, 2010, the Patient Protection and Affordable Care Act (ACA) was signed into law, representing the largest change to health care delivery in the United States since the introduction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
74
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 90 publications
3
74
1
Order By: Relevance
“…Although this study found an increase in stage I diagnoses as a result of Medicaid expansion, earlier reports on this topic have conflicting results. 4,9 Soni and colleagues 8 found more early-stage diagnoses in a heterogeneous cohort of malignancies. When analyzing the NCDB for the years 2011-2014, Jemal and colleagues 5 found increased early-stage colorectal cancer in Medicaid expansion states, but this was not significant on adjusted analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study found an increase in stage I diagnoses as a result of Medicaid expansion, earlier reports on this topic have conflicting results. 4,9 Soni and colleagues 8 found more early-stage diagnoses in a heterogeneous cohort of malignancies. When analyzing the NCDB for the years 2011-2014, Jemal and colleagues 5 found increased early-stage colorectal cancer in Medicaid expansion states, but this was not significant on adjusted analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Early reports have suggested that cancer screening and early diagnosis have improved with Medicaid expansion, but some of the findings are inconsistent. [4][5][6][7][8][9][10][11] Colon cancer is a disease that can be particularly affected by access to care, given its high prevalence and effective screening protocols. In addition, nearly one-half of cases occur in patients younger than 65 years and the incidence among younger adults has been increasing in recent years.…”
mentioning
confidence: 99%
“…Lung cancer (LCa) remains one of the primary reasons of cancer mediated fatalities globally, with 5-year survival rates of <20% in 2017 (1). In the US ~234,030 new LCa cases were diagnosed and in China ~781,500 new LCa cases were diagnosed in 2018 (2). Non-small cell lung cancer (NSCLC) is the most prevalent subtype of lung cancer, and lung adenocarcinoma (LUAD) is the major subtype of NSCLC (3).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found increased screening and early-stage diagnosis, but these findings are at times small or inconsistent. [7][8][9][10][11][12] Findings specific to pancreatic cancer have also been mixed. One national study found no difference in early stage diagnoses in the years immediately following insurance expansion.…”
mentioning
confidence: 99%